GAMBARAN KEPEMIMPINAN TRANSFORMASIONAL KEPALA UPTD SMP NEGERI 3 TOBADAK KABUPATEN MAMUJU TENGAH - M, Mahadir; Wahira, Wahira; Ardiansyah, Muh (Jurnal Administrasi, Kebijakan, dan Kepemimpinan Pendidikan (JAK2P), 2025)
This research is a qualitative research with the aim of knowing the description of the transformational leadership of school principals in the aspects of individual consideration and inspirational motivation at UPTD SMP Negeri 3 Tobadak, Central Mamuju Regency, West Sulawesi Province. Data collection techniques use interviews, observation and documentation studies. The subjects of this research were the principal, deputy principal for curriculum affairs, deputy principal for student affairs, deputy principal for facilities and infrastructure, head of administration, and teachers. The research results show that: (1) In the aspect of individual attention, the principal's transformational leadership practices are reflected through the work environment and organizational climate which is built with an orientation towards family principles. The principal always provides opportunities for subordinates to speak and be heard at every school meeting. Apart from that, school principals also always provide opportunities for teachers to take part in training, seminars, workshops and other development programs; and (2) In the aspect of inspirational motivation, the principal's transformational leadership practice is reflected through the involvement of teachers and staff in preparing the school's vision, mission, goals and work programs as stated in the Educational Unit Operational Curriculum (KOSP) document. Apart from that, the school principal also intensely gives appreciation or appreciation for the achievements of the followers, both in verbal and non-verbal form.